Lipid Profile and Antihypertensive Drugs - Abdul-Khader, Abdul-Khader A. (AL-Kindy College Medical Journal, 2009)
Background: Hypertension and dyslipidemia arecardiovascular risk factors that commonly coexist .Objective : To evaluate the effects of ß - blocker(Atenolol) , ACE inhibitor (Captopril) calcium Channelblocker (Nefidipin ) and diuretics on serum lipid profiles .Method: Thirty untreated hypertensive and 147hypertensive patient treated with these antihypertensivedrugs, attending different public health clinics in Basrahpronivce were enrolled in this study .Serum lipid profile were determined enzymaticaly using kitsfrom BioMerieux, France .Result : The study has revealed that ß-blocker do notsignificantly affect total cholesterol ( TC ) and LDLcholesterol , but increase significantly triglyceride (TG) andVLDL – cholesterol and decrease HDL – cholesterol.Diuretics causes a significant elevation of TG with generallyno significant changes in TC , LDL – cholesterol , VLDL –cholesterol and HDL-cholesterol. ACE inhibitor and calciumchannel blockers appears to have no significant effect onplasma lipids .Conclusion :It may important to measure blood lipid levelsto identify pre-existing hyperlipidemia before starting theantihypertensive therapy and to select antihypertensive agentthat will not influence the lipid profile or interfere with thetherapy of hyperlipidemi